Assessment of individual molecular response in chronic myeloid leukemia patients with atypical BCR-ABL1 fusion transcripts: recommendations by the EUTOS cooperative network - Schäfer, Vivien; White, Helen E; Gerrard, Gareth; Möbius, Susanne; Saussele, Susanne; Franke, Georg-Nikolaus; Mahon, François-X; Talmaci, Rodica; Colomer, Dolors; Soverini, Simona; Machova Polakova, Katerina; Cross, Nicholas C P; et al. (Journal of cancer research and clinical oncology, 2021)
PURPOSE: Approximately 1-2% of chronic myeloid leukemia (CML) patients harbor atypical BCR-ABL1 transcripts that cannot be monitored by real-time quantitative PCR (RT-qPCR) using standard methodologies. Within the European Treatment and Outcome Study (EUTOS) for CML we established and validated robust RT-qPCR methods for these patients. METHODS: BCR-ABL1 transcripts were amplified and sequenced to characterize the underlying fusion. Residual disease monitoring was carried out by RT-qPCR with specific primers and probes using serial dilutions of appropriate BCR-ABL1 and GUSB plasmid DNA calibrators. Results were expressed as log reduction of the BCR-ABL1/GUSB ratio relative to the patient-specific baseline value and evaluated as an individual molecular response (IMR). RESULTS: In total, 330 blood samples (2-34 per patient, median 8) from 33 CML patients (19 male, median age 62 years) were analyzed. Patients expressed seven different atypical BCR-ABL1 transcripts (e1a2, n = 6; e6a2, n = 1; e8a2, n = 2; e13a3, n = 4; e14a3, n = 6; e13a3/e14a3, n = 2; e19a2, n = 12). Most patients (61%) responded well to TKI therapy and achieved an IMR of at least one log reduction 3 months after diagnosis. Four patients relapsed with a significant increase of BCR-ABL1/GUSB ratios. CONCLUSIONS: Characterization of atypical BCR-ABL1 transcripts is essential for adequate patient monitoring and to avoid false-negative results. The results cannot be expressed on the International Scale (IS) and thus the common molecular milestones and guidelines for treatment are difficult to apply. We, therefore, suggest reporting IMR levels in these cases as a time-dependent log reduction of BCR-ABL1 transcript levels compared to baseline prior to therapy.
Keywords: Humans; messenger RNA; inhibitory proteinkinas; lidé středního věku; Biomarkers, Tumor; následné studie; Female; Aged; dospělí; senioři; lidé; nádorové biomarkery; Adult; Protein Kinase Inhibitors; RNA, Messenger; ženské pohlaví; Male; chronická myeloidní leukemie; Middle Aged; bcr-abl fúzní proteiny; prognóza; Fusion Proteins, bcr-abl; míra přežití; Leukemia, Myelogenous, Chronic, BCR-ABL Positive; mužské pohlaví; Prognosis; Follow-Up Studies; Survival Rate